The Effect of Governance, Risk Management, and Compliance on Efforts to Minimize Potential Fraud Based on the Fraud Pentagon Concept - Agung Hermawan; Novita Novita (Association of Certified Fraud Examiners Indonesia Chapter, 2021)
This study aims to determine the effect of corporate governance, risk management, and compliance with applicable regulations on efforts to minimize the potential fraud based on the Fraud Pentagon concept. For companies engaged in financial service providers, the results of this study are expected to contribute to the implementation of governance, risk management, and compliance (GRC) in order to minimize potential fraud and achieve the expected goals. Respondents used in this study are the employees of Bank Perkreditan Rakyat (BPR). Data are collected using interviews, observations, and questionnaires. Descriptive analysis, data quality analysis, and structural model analysis are used to test hypotheses with the application of STATA version 14. The results show that the variables of corporate governance and risk management have a significant effect on the efforts to minimize potential fraud, while the variable of compliance has no significant effect on the efforts to minimize potential fraud. Due to several factors, such as the small scope of BPR compared to conventional banks and the small number of employees, the implementation of GRC has not been achieved optimally.